STUDI USAHA SEKTOR INFORMAL DI PASAR AIR HAJI KECAMATAN LINGGO SARI BAGANTI KABUPATEN PESISIR SELATAN - Akmal, Yosi Meda; Rianto, Slamet; U, Iswandi (STKIP PGRI Sumbar, 2013)
This study aims to determine the informal sector businesses in the Pasar Air Haji Linggo Sari Baganti District Pesisir Selatan region which includes: 1) the characteristics of informal sector business unit, 2) the characteristics of workers and informal sector business owners, 3) informal sector employment and 4) capital and income from the informal sector.This research is descriptive. The population in this study were all business units in the informal sector, amounting Pasar Air Haji 56 business units . Samples were taken with a total sampling techniques so that sample was 56 the owner of the business unit.The research found that: 1 ) The characteristics of informal sector business units in the Pasar Air Haji Sari Linggo Baganti mostly stalls ( 42.9 % ), located around the market ( 37.5 % ) and have been trying 2 years ( 39.35 %). This means that business units in the informal sector is dominated by Pasar Haji Air stalls located around the old market and tried to > 2 years, (2) characteristics of workers and owners of informal sector enterprises, informal business owners are generally aged > 30 years ( 64.3 %), with marital status married ( 89.29 %), derived from the Linggo Sari Baganti District, education level informal sector business owners on average completed high school (71.43%) and previous work in the sector also means that the owner of this informal.Hal sector informal aged 30 years and above , the level of secondary education , married and effort previously also in the informal sector, (3) absorption of labor in the informal sector is evident from the number of workers is generally 2 people (41.07%), came from the area around the market Air Haji (55.36%), the average education level of junior high school graduation (60.71%), labor hours (60.71%), the old owners work longer than labor (82.14%), payroll systems that do is a daily system (46.43%) with a salary of Rp 25,000 - Rp 50.000/hari (53.57%) and (4) capital markets business in the informal sector Pasar Air Haji Linggo Sari Baganti district derived from equity (64.29%), the amount of initial capital > Rp 10,000,000 (67.86%), capital now > Rp 10,000,000 (87.5%), somewhat informal business development pesar (83.14%) and the capital is currently insufficient (73, 21%)